Religiosity as a determinant of happiness - Matthias Opfinger; Erich Gundlach (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2011)
We find a U-shaped relation between happiness and religiosity in cross-country panel data after controlling for income levels. At a given level of income, the same level of happiness can be reached with high and low levels of religiosity, but not with intermediate levels. A rise in income causes an increase in happiness along with a decline of religiosity. Our interpretation of the empirical results is that the indifference curves for religiosity and other commodities of the utility function are hump-shaped.
Keywords: I31; Z12; O11; 330; Happiness; religiosity; utility function; long-run development